Amendment Politics and Agenda Setting: A Theory with Evidence from the US House of Representatives. (10th January 2018) - Magleby, Daniel B; Monroe, Nathan W; Robinson, Gregory
Abstract: Much recent work on legislative policy making has focused on the implications of agenda power. Yet, a critical step of the legislative process—floor amendments—has been almost entirely ignored in the most prominent theories of legislative decision making. In this paper, we fill this gap by developing a theoretical treatment of agenda setting at the amendment stage. Specifically, our theoretical approach defines the relationship between agenda setting at the amendment stage and outcomes at final passage. We test several implications using data from the US House of Representatives, and show that amendments do mitigate some of the majority party's agenda setting advantage by moderating initial proposals away from the majority party position. However, amendments do not systematically undermine the majority party's negative agenda control, as we find that amendment rolls do not increase the incidence of final passage rolls for the majority party.